Inhibitory Effects of Some Thai Plant Extracts on AAPH-induced Protein Oxidation and Protein Glycation - Chaiyasut, Chaiyavat; Chansakaow, Sunee (Asian Health, Science and Technology Reports, 2007)
Oxidants can cause damage to biomolecules and alter cellular metabolism. Keys among the targets for oxidative damage are structural proteins and enzymes. It is expected that several constituents from Thai plants may be able to prevent such oxidative damages. The present study was carried out to investigate the inhibitory activity on 2,2'-azobis (2-amidinopropane) dihydrochloride (AAPH)-induced protein oxidation and nonenzymatic protein glycation of Thai medicinal plant extracts, including the extracts of Phyllanthus emblica Linn., Kaempferia parviflora, and Globba wintii C.H. Wright. The plant extracts were investigated for their inhibitory activities on AAPH-induced protein oxidation to allophycocyanin. The loss of allophycocyanin fluorescence was measured and interpreted as a half-life of the protein. The half-life of allophycocyanin in the presence of 1.0 g/ml of P. emblica, K. parviflora and G. wintii C.H. Wright extracts were 21.24, 11.31, and 11.39 minutes, respectively. The assay of protein glycation at 37 oC for 2 weeks was also performed. The percent inhibition of protein glycation by the plant extracts was reported. P. emblica achieved 88.09 % inhibition against protein glycation formation at 10.0 g/ml whereas, K. parviflora and G. wintii C.H. Wright achieved 28.10 % and 15.74 % inhibition at 50 g/ml, respectively. Among the tested extracts, P. emblica Linn. extract had higher oxidative protein damage protection and higher protein glycation inhibitory effect than K. parviflora and G. wintii C.H. Wright extracts. Thus, it has a higher potential use as anti-aging therapy.